2011
DOI: 10.4315/0362-028x.jfp-11-024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an Automated Most-Probable-Number Technique with Traditional Plating Methods for Estimating Populations of Total Aerobes, Coliforms, and Escherichia coli Associated with Freshly Processed Broiler Chickens

Abstract: An instrument (TEMPO) has been developed to automate the most-probable-number (MPN) technique and reduce the effort required to estimate some bacterial populations. We compared the automated MPN technique with traditional microbiological plating methods and Petrifilm methods for estimating the total viable count of aerobic microorganisms (TVC), total coliforms (CC), and Escherichia coli populations (EC) on freshly processed broiler chicken carcasses (postchill whole carcass rinse [WCR] samples) and cumulative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Indeed, all TEMPO ® bacterial tests have been approved by international quality and standards organizations, such as AOAC International, AFNOR and ISO for food and environmental samples [35][36][37][38]. Evaluations of the performances of the TEMPO ® MPN method for the characterization of bacterial content in food products, including dairy milk, have been reported [39][40][41][42][43][44][45]. Most of them have demonstrated a good agreement in the results between the plate count method and TEMPO ® for all types of targeted bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, all TEMPO ® bacterial tests have been approved by international quality and standards organizations, such as AOAC International, AFNOR and ISO for food and environmental samples [35][36][37][38]. Evaluations of the performances of the TEMPO ® MPN method for the characterization of bacterial content in food products, including dairy milk, have been reported [39][40][41][42][43][44][45]. Most of them have demonstrated a good agreement in the results between the plate count method and TEMPO ® for all types of targeted bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The mean values of samples analyzed according to TEMPO TVC and the conventional ISO 4833:2003 methods were found to be 3.97 log cfu/g and 3.95 log cfu/g respectively. In a study conducted by Line et al (15), a number of 120 samples of chicken raw carcass from production line before, and after freezing process were analyzed by using TEMPO TVC and the conventional microbial colony enumeration methods. It was found that the mean values obtained by both methods were 3.09 log cfu/g and 3.02 log cfu/g before freezing, whereas they were 1.53 log cfu/g and 1.31 log cfu/g after freezing, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Linear regression and Pearson correlation analyses were performed in order to measure the compliance levels of both methods. In a study conducted by Line et al (15) involving a number of 120 samples of chicken raw carcass from production line before and after freezing process, the carcass samples before freezing were analyzed according to TEMPO TVC and the conventional microbial colony count methods, and a high correlation coefficient of 0.972 was found. However, when using the samples after freezing, the correlation coefficient was found to be 0.710 between TEMPO TVC and the conventional rapid test methods.…”
Section: Discussionmentioning
confidence: 99%
“…37 Total coliforms were selectively counted on Petrifilm CC [3 M, Segrate (MI), Italy], 38 whereas SRB were enumerated using tryptose-sulfitecycloserine (Sigma-Aldrich, Milan, Italy). 39 All plates seeded with lactobacilli were incubated for 48 to 72 hours at 371C under anaerobic conditions (GasPak system) with Anaerocult A kits (Merck Millipore, Darmstadt, Germany), whereas LAPTg plates were incubated in aerobic conditions for 24 to 48 hours at 371C.…”
Section: Enumeration Of Specific Bacterial Groups In Gastric Juicementioning
confidence: 99%